Market interaction and the focus on consequences in moral decision making - Nana Adrian; Ann-Kathrin Crede; Jonas Gehrlein (University of Bern, Department of Economics, 2019)
There is a long ongoing debate on whether interaction in a market influences moral decisions of individuals. While some studies show that individuals tend to decide less morally when being exposed to a market environment, other studies argue that the experience of market interaction promotes moral behavior. We add to this discussion by distinguishing between two moral concepts: consequentialism and deontology. According to consequentialism, actions are evaluated only by their consequences. Contrary to that, deontology focuses solely on the morality of the action itself. We design an online experiment in order to investigate the effect of market interaction on moral decision making in a subsequent moral dilemma. Taking into account how markets make cost benefit considerations salient, we hypothesize that individuals are more likely to focus on consequences if they interacted in a market before.
Keywords: D91; L1; 330; Consequentialism; deontological motivations; double auction; salience; decision theory